Morbidity and mortality in elderly patients admitted to the emergency room of a university hospital in the Brazilian Unified Health System in western Paraná, in 2023 (Research, Society and Development, 2025)
The increasing aging of the population and the coexistence of multiple chronic diseases in elderly patients, they tend to require more hospitalization than young adults, as well as a greater chance of clinical complications and mortality and higher costs with hospitalizations. Therefore, the objective of this study was to collect data on the clinical-epidemiological profile and clinical outcome of the main causes of hospitalizations of elderly patients admitted to the emergency room in a university hospital that operates within the scope of the Unified Health System (SUS) and to verify the relationship of other relevant variables in the clinical outcome of the patient, such as comorbidities and clinical complications. This is an observational, retrospective, cross-sectional, quantitative study, in which a sample of 40% of patients aged 60 years or older admitted in 2023 was randomly selected. The results indicate that 32.66% of the patients were hospitalized due to cardiac causes, with arterial hypertension as the main associated comorbidity and the main laboratory tests being statistically significant in relation to the outcome. In conclusion, laboratory tests altered in relation to the reference range at admission, such as hemoglobin, leukocytes, neutrophils, rods, lymphocytes, arterial lactate, urea, creatinine, glucose, CRP and albumin, are associated with hospital outcome.